FAILURE ANALYSIS OF ALUMINIUM AND ZINC HEAT REFLECTOR IN TIMBER DRYKILN - Sulistioso Giat S.; A Sitompul; M. N. Indro; A Rahmatika (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2012)
FAILURE ANALYSIS OF ALUMINIUM AND ZINC HEAT REFLECTOR IN TIMBER DRYKILN. Aluminium and Zinc (Al-Zn) alloy coated steel sheet (JIS G3141) was used as a heat reflector in timber dry kiln. After six months continuous service at 110°C in moist condition, the heat reflector is corroded. Failure analysis method was used to analyze this corrosion phenomena. Macroscopic and microscopic examination with some characterization have been performed to determine the elemental composition and corrosion products. The elemental composition of corroded heat reflector that were detected by SEM-EDS are sulphur, chloride, calcium, and potassium. XRD analysis revealed the zinc aluminium carbonate hydroxide hydrate (Zn6Al2(OH)16CO3.4H2O) known as black rust staining and iron oxide (Fe3O4), as corrosion products. Environmental condition in timber dry kiln with the existence of acid and alkaline elements cause the corrosion process occur. Those elements come fromthe dried timber and steam that adhered on the heat reflector surface attacked the Al-Zn coating and base metal. Humidity and high temperature in timber dry kiln environment increase the corrosion rate of the heat reflector.